2014
DOI: 10.1186/1471-2334-14-307
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of two informative SNP-based strategies for typing Pseudomonas aeruginosa isolates from patients with cystic fibrosis

Abstract: BackgroundMolecular typing is integral for identifying Pseudomonas aeruginosa strains that may be shared between patients with cystic fibrosis (CF). We conducted a side-by-side comparison of two P. aeruginosa genotyping methods utilising informative-single nucleotide polymorphism (SNP) methods; one targeting 10 P. aeruginosa SNPs and using real-time polymerase chain reaction technology (HRM10SNP) and the other targeting 20 SNPs and based on the Sequenom MassARRAY platform (iPLEX20SNP).MethodsAn in-silico analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 19 publications
0
31
0
Order By: Relevance
“…No dominant Australian shared CF P. aeruginosa strains (e.g. AUST‐01, AUST‐02 and AUST‐06) were observed. In contrast, our analysis demonstrated that 20 (67%) participants had infection with P. aeruginosa strains, with genotype profiles that showed close genetic relationships to locally derived genotypes found in the environment, animals and other non‐CF clinical presentations .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…No dominant Australian shared CF P. aeruginosa strains (e.g. AUST‐01, AUST‐02 and AUST‐06) were observed. In contrast, our analysis demonstrated that 20 (67%) participants had infection with P. aeruginosa strains, with genotype profiles that showed close genetic relationships to locally derived genotypes found in the environment, animals and other non‐CF clinical presentations .…”
Section: Resultsmentioning
confidence: 98%
“…A hole‐correction factor was applied to account for possible ‘stacking’ of bacterial colonies on the agar plates inside the ACI . All confirmed P. aeruginosa isolates underwent genotyping using an iPLEX20SNP assay (Sequenom, San Diego, CA, USA) as previously published …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations